Ganxiao Dong: A Hotspot of Cave Biodiversity in Northern Guangxi, China - Sunbin Huang; Guofu Wei; Hengsong Wang; Weixin Liu; Anne Bedos; Louis Deharveng; Mingyi Tian (Diversity, 2021)
Located in the core zone of Mulun National Nature Reserve in northern Guangxi, the limestone cave Ganxiao Dong harbours the richest cave fauna currently known in China. In total, 26 species of cave invertebrates have been recognized so far, in spite of limited sampling efforts. Of them, 20 are troglobionts or stygobionts, including one snail, four millipedes, three spiders, one harvestman, three isopods, two springtails, two crickets, one non-glowing sticky worm, and three trechine beetles. Six other species are troglophiles. The most remarkable characteristic of this fauna is its high number of troglomorphic species, especially among millipedes, crickets and beetles.